Mechanistic details of the nickel-mediated formation of acrylates from CO2, ethylene and methyl iodide - Pleßow, Philipp; Weigel, Laura Kathrin; Lindner, Ronald; Schäfer, Ansgar; Rominger, Frank; Limbach, Michael; Hofmann, Peter (Organometallics, 2013)
Methyl iodide induces the stoichiometric cleavage of nickelalactones, which are key intermediates in the nickel-mediated reaction of CO2 and alkenes to acrylates. Herein, we propose a modified and extended mechanism for this reaction on the basis of theoretical and experimental investigations for the bidentate P ligand 1,2-bis(di-tert-butylphosphino)ethane (dtbpe). The calculated elementary steps agree well with experimental findings: reaction barriers are reasonable and explain the facile liberation of acrylate from a nickelalactone by methyl iodide. We were able to isolate reactive intermediates and to verify the existence of proposed reaction pathways. Additionally, we have identified unproductive pathways leading to byproducts (e.g., propionates and catalytically inactive organometallic species). Although those side reactions can be suppressed to a certain extent, the strong binding of acrylate to nickel prevents a catalytic reaction, at least for the chosen ligand.